2014
DOI: 10.1055/s-0034-1396520
|View full text |Cite
|
Sign up to set email alerts
|

Is Primary Hyperparathyroidism a Risk Factor for Papillary Thyroid Cancer? An Exemplar Study and Literature Review

Abstract: Introduction Primary hyperparathyroidism (PHPT) is associated with several cancer types, including papillary thyroid carcinoma (PTC). Objective To explore further the relation between PHPT and PTC. Methods By considering patients with PHPT as extra-suspicious for PTC, we studied an exemplar group of patients with PHPT with a small (≤1 cm) thyroid nodule, which was negative in preoperative cytologic examination. During parathyroidectomy, a frozen section biopsy of the thyroid nodule confirmed PTC, as did the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The majority of the reported studies were made in patients with PHPT in different stages of evolution [15, 16]. In the present study, in which we included patients with symptomatic PHPT, we found a prevalence of CPT in 20%.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The majority of the reported studies were made in patients with PHPT in different stages of evolution [15, 16]. In the present study, in which we included patients with symptomatic PHPT, we found a prevalence of CPT in 20%.…”
Section: Discussionsupporting
confidence: 57%
“…PTC occurs in 7 to 15% of cases and is related to risk factors as age, sex, radiation exposition, family history, among others [13]. It calls to attention that, in patients with PHPT, the prevalence of thyroid nodular disease is similar that in general population; nevertheless, CPT is more frequent than in general population [15, 16]. The high concurrence of these two diseases in the same patients may not be a coincidence; a lot of factors may connect PHTP with CPT.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant pHPT and thyroid malignancy have been reported in several studies since the first cases were reported by Ogburn and Black [ 7 ] in 1956. In pHPT patients, several studies reported the prevalence of papillary thyroid cancer (PTC) to range from 2% to 15% [ 8 , 9 ]. Data on the association between sHPT and PTC is more limited.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported 15–75% of patients with PHPT have concomitant thyroid nodules ( 8 , 9 ). Moreover, several authors have described a rate of thyroid cancer in patients with PHPT that appears to be higher than the general population ( 4 , 10 , 11 , 12 , 13 , 14 , 15 ). A review of data from nine studies, including a total of 2510 patients with PHPT requiring parathyroidectomy, indicated an incidence for thyroid cancer of 5%, compared to international estimates ranging from ~2 to 12 per 100,000 thyroid cancer new cases per year ( 15 ).…”
Section: Introductionmentioning
confidence: 99%